Overcoming Educational Challenges and Impact of COVID-19 in a Pathology Residency Program. (25th February 2021) - Mindiola Romero, Andres E.; Black, Candice C.; Jackson, Christopher R.
Our program in is a 4-year combined anatomic pathology (AP) and clinical pathology (CP) program located in New Hampshire. Prior to the novel coronavirus (COVID-19) pandemic, double-headed sign-outs and multi-headed scope didactic conferences took place daily. On the autopsy service, cases were performed in-house under attending supervision, and forensic cases were performed at the off-site Office of the Medical Examiner. In CP, residents engaged in weekly didactic CP lectures and engaged in in-person resident-attending discussions, laboratory rounds, and direct patient contact on a daily basis. Institutional Universal Guidelines from the Emergency Order from New Hampshire were imposed at the beginning of the pandemic. These included exposure mitigation and employee screening strategies. Changes to resident rotations and didactic sessions, strategies to maintain resident wellness, and the program director perspectives are described. Amid the pandemic, digital pathology, teleconferencing platforms, and social media became important resources for pathology education. Digital platforms allowed groups of people to communicate and watch live presentations while social distancing. In AP, whole slide imaging allowed both attendings and residents to scan slides for personal learning, slide conferences, and didactic learning sessions. Following these measures, we supported the clinical needs of our medical center and learning needs of our residents while enacting social distancing and prevention guidelines early in the pandemic. Although the full impact of COVID-19 on pathology residency programs is still unknown, we incorporated new facets of communication technologies. These were immensely helpful in maintaining social distancing and helping to reduce the spread of disease.